Analisis QSPM Untuk Peningkatan Pendapatan Petani Kopi Arabika di Kabupaten Aceh Tengah - Muhammad Yuzan Wardhana; Widyawati; Dinda Triviana; Fairuzzabadi (lembaga penelitian universitas swadaya gunung jati, 2024)
This research for strategies to increase the income of Arabica coffee farmers in Central Aceh Regency uses SWOT analysis with the aim of the research being to determine the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) on the progress of coffee farmers in Central Aceh. Next, formulate an appropriate main alternative strategy (QSPM) for a strategy to increase the income of coffee farmers in Central Aceh. The sampling method used primary and secondary data, primary data was obtained through interviews and direct observation, while secondary data was obtained from BPS (Central Statistics Agency) Aceh, Central Aceh Province Agriculture and Plantation Service as well as journal literature and other reading sources. The research results show that the income strategy of Arabica farmers in Central Aceh Regency is located in quadrant I (Aggressive Strategy), namely using strength to take advantage of opportunities, with coordinates (1.8 : 2.0). Meanwhile, the results of the QSPM analysis show that the main alternative strategy is the use of quality seeds to maximize arabica production.Keywords: Aceh Tengah, Arabica Coffee, QSPM, SWOT